International Watercourse Law and A Perspective on Nepal-India Relation - Thanju, Jeewan P. (Hydro Nepal: Journal of Water, Energy and Environment, 2013)
Hydro Nepal; Journal of Water, Energy and Environment Vol. 12, 2013, January Page: 89-91DOI: http://dx.doi.org/10.3126/hn.v12i0.9041 Uploaded Date : 10/29/2013